Oxidative stress in dairy cows seropositives for Neospora caninum - Glombowsky P.* (2017)
© 2017 Elsevier LtdBovine neosporosis is caused by the protozoan Neospora caninum and is one of the major causes of abortion in cows. Cattle are intermediate hosts of this parasite and may have asymptomatic or symptomatic infections. Therefore, the aim of this study was to evaluate oxidative stress marker reactive oxygen species (ROS), thiobarbituric reactive acid substances (TBARS) levels, glutathione S-transferase (GST), adenosine deaminase (ADA), and butyrylcholinesterase (BChE) activities in dairy cows seropositives for N. caninum (asymptomatic or symptomatic). Dairy cows (n = 90) were tested by immunofluorescent antibody assay (IFA) for N. caninum and divided accordingly into three groups: the group A (seronegatives, n = 30), the group B (seropositives and asymptomatic, n = 30), and the group C (seropositives and symptomatic, n = 30). It was observed increased levels of TBARS and reduced (P < 0.05) BChE activity in seropositives either asymptomatic or symptomatic animals. ROS levels and ADA activity increased, and GST activity decreased (P < 0.05) only in seropositives symptomatic dairy cows (the group C) compared to seronegatives dairy cows (the group A). Based on these results, it was observed that seropositive animals showed cell damage associated with oxidative stress and inflammation, mainly in those with symptomatic infections. Increased seric ROS levels and BChE activity may have influenced N. caninum pathogenesis in symptomatic animals due to increased cell damage and exacerbated inflammatory response, leading to the development of clinical signs.